ปัจจัยที่ส่งผลต่อประสิทธิผลการบริหารงานวิชาการของผู้บริหารสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษาร้อยเอ็ด - โยคะสัย, ขวัญเรือน; เมยไธสง, สุเทพ (วารสารการบริหารการศึกษา มมร.วิทยาเขตร้อยเอ็ด, 2023)
บทความวิจัยนี้มีวัตถุประสงค์ 1) เพื่อคัดสรรปัจจัยที่ส่งผลต่อประสิทธิผลการบริหารงานวิชาการของผู้บริหารสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษาร้อยเอ็ด 2) เพื่อศึกษาความสัมพันธ์ของปัจจัยที่ส่งผลต่อประสิทธิผลการบริหารงานวิชาการ ของผู้บริหารสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษาร้อยเอ็ด 3) เพื่อสร้างสมการพยากรณ์ของปัจจัยที่ส่งผลต่อประสิทธิผลการบริหารงานวิชาการของผู้บริหารสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษาร้อยเอ็ด กลุ่มตัวอย่าง  ได้แก่ ครูในสังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษาร้อยเอ็ด ปีการศึกษา 2565 จำนวน 430 คน เครื่องมือที่ใช้ในการเก็บรวบรวมข้อมูลเป็นแบบสอบถามเป็นแบบมาตราส่วนประมาณค่า 5 ระดับ การวิเคราะห์ข้อมูล ได้แก่  ส่วนเบี่ยงเบนมาตรฐาน สหสัมพันธ์แบบเพียร์สัน และการวิเคราะห์ถดถอยพหุคูณแบบปกติ            ผลการวิจัยพบว่า 1) ปัจจัยที่ส่งผลต่อประสิทธิผลงานวิชาการของผู้บริหารสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษาร้อยเอ็ด ประกอบด้วย ปัจจัยด้านครูผู้สอน ปัจจัยด้านสื่อและเทคโนโลยีทางการศึกษา ปัจจัยด้านผู้บริหาร ปัจจัยด้านผู้ปกครองและชุมชน  ปัจจัยด้านงบประมาณ  และปัจจัยด้านอาคารสถานที่และสิ่งแวดล้อม 2) ประสิทธิผลการบริหารงานวิชาการของผู้บริหารสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษาร้อยเอ็ด ประกอบด้วย การพัฒนาหลักสูตรของสถานศึกษา  การพัฒนากระบวนการเรียนรู้ การพัฒนาสื่อ เทคโนโลยีนวัตกรรมเพื่อการศึกษา การประเมินผลการเรียนรู้ การวิจัยเพื่อพัฒนาผู้เรียน 3) ปัจจัยพยากรณ์ของการพยากรณ์ประสิทธิผลการบริหารงานวิชาการของผู้บริหารสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษาร้อยเอ็ด พบว่า ค่าสัมประสิทธิ์สหสัมพันธ์ระหว่างตัวแปรพยากรณ์ทั้ง 6 ตัวแปร และประสิทธิผลการบริหารงานวิชาการของผู้บริหารสถานศึกษา มีความสัมพันธ์ในทางบวก และมีนัยสำคัญทางสถิติที่ระดับ .01  มีค่าสัมประสิทธิ์สหสัมพันธ์อยู่ ระหว่าง 0.112-0.544 และปัจจัยที่ส่งผลต่อประสิทธิผลการบริหารงานวิชาการของผู้บริหารสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษาร้อยเอ็ด มีค่าสัมประสิทธิ์สหสัมพันธ์สูงไปต่ำ ดังนี้  ได้แก่ ปัจจัยด้านครูผู้สอน อยู่ในระดับปานกลาง ไปใน ทิศทางบวก อย่างมีนัยสำคัญทางสถิติที่ระดับ .01 รองลงมา ได้แก่ ปัจจัยด้านสื่อและเทคโนโลยีทางการศึกษ  ปัจจัยด้านงบประมาณ ปัจจัยด้านผู้บริหาร ปัจจัยด้านผู้ปกครองและชุมชน และต่ำที่สุด ได้แก่ ปัจจัยด้านอาคารสถานที่และสิ่งแวดล้อม  4) ผลการวิเคราะห์พหุคูณถดถอยแบบปกติ (Enter Regression Method) สามารถสร้างสมการพยากรณ์ของปัจจัยที่ส่งผลต่อประสิทธิผลการบริหารงานวิชาการของผู้บริหารสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษาร้อยเอ็ด ดังนี้              Y = a + b 2 X 2 + b 6 X 6 + b 1 X 1 + b 4 X 4 + b 3 X 3 + b 5 X 5            Y = 1.0421+0.1577X 2 +0.1483X 6 +0.1182X 1 +0.1227X 4 +0.1094X 3 +0.1035X 5            Z =   β 2 Z 2 + β 6 Z 6 + β 1 Z 1 + β 4 Z 4 + β 3 Z 3 + β 5 Z 5            Z= 0.1577Z 2 + 0.2131Z 6 + 0.1875Z 1 + 0.1734Z 4 + 0.1346Z 3 + 0.1125Z 5           The objectives of this research were 1) to identify the factors affecting the effectiveness of academic management by administrators affiliated with the Office of Roi Et Secondary Educational  Service Area, 2) To study the relationship of factors affecting the effectiveness of academic administration of school administrators Under the Office of Roi Et Secondary Educational Service Area 3) To create a forecasting equation of factors affecting academic administration effectiveness of school administrators. Under the Office of Roi Et Secondary Educational Service Area The sample group consisted of 430 teachers under the Office of Roi Et Educational Service Area in the academic year 2022. The data collection tool was a questionnaire with a 5-point Likert scale. Data analysis included standard deviation, Pearson's product moment correlation of coefficient, and normal multiple regression analysis (Enter Regression Method).            The following were the summarized results of the research: 1) The factors that affect the academic performance of school administrators under the Office of Secondary Educational Service Area in Roi Et province are teachers, educational media and technology, administrators, parents and communities, budget, and facilities and environment. 2) The effectiveness of academic management by school administrators under the supervision of the Office of the Educational Service Area in Roi Et province consists of curriculum development, development of learning processes, development of technology and innovation, assessment of learning outcomes, and research for student development. 3) The predictive factors of the effectiveness of academic management by school administrators under the supervision of the Educational Service Area Office in Roi Et province found that the correlation coefficient between all 6 predictive variables and the effectiveness of academic management by educational administrators had a positive correlation and the statistical significant level was at the .01. The correlation coefficients ranged from 0.112 to 0.544. The factors that have a high correlation with the effectiveness of academic management by school administrators under the supervision of the Office of Educational Service Area Office in Roi Et province are as follows: the development of school curricula, followed by the development of learning processes, development of educational media and technology innovation, assessment of learning outcomes, and the research for student development. On the other hand, the factors that have a low correlation with the effectiveness of academic management by educational administrators under the supervision of the Office of Educational Service Area in Roi Et province are as follows: teachers, which is at a moderate level and has a statistical significant positive correlation at the .01 level, followed by factors related to educational media and technology, budget, administrative, and factors related to parents, communities, and environment, which have the lowest correlation. 4) The results of the Enter Regression Method can create an equation to predict the factors that affect the effectiveness of academic management by school administrators affiliated with the Office of Educational Service Area in Roi Et as follows:            Y = a + b 2 X 2 + b 6 X 6 + b 1 X 1 + b 4 X 4 + b 3 X 3 + b 5 X 5             Y = 1.0421+0.1577X 2 +0.1483X 6 +0.1182X 1 +0.1227X 4 +0.1094X 3 +0.1035X 5             Z =   β 2 Z 2 + β 6 Z 6 + β 1 Z 1 + β 4 Z 4 + β 3 Z 3 + β 5 Z 5             Z= 0.1577Z 2 + 0.2131Z 6 + 0.1875Z 1 + 0.1734Z 4 + 0.1346Z 3 + 0.1125Z 5